Mengatasi Masalah Pembelajaran Guru PJOK Sarana dan Prasarana di Sekolah SDN 101776 Sampali - Apri Ebrata Purba; Samsuddin Siregar; Ahmad Hidayat; Royhan Taher (Journal of Creative Student Research, 2024)
This research aims to identify and overcome learning problems faced by Physical Education, Sports and Health (PJOK) teachers at SDN 101776 Sampali, which are caused by a lack of facilities and infrastructure. The method used in this research is observation and interviews with teachers and students, as well as analysis of related documents. The research results show that limited facilities such as sports fields, equipment and adequate classrooms hinder the learning process. To overcome this problem, it is recommended that there be cooperation between the school, parents and the community to increase support for the provision of facilities and infrastructure. It is hoped that this research can contribute to improving the quality of PJOK learning at SDN 101776 Sampali.